Inferior J waves in patients with vasospastic angina might be a risk factor for ventricular fibrillation. Issue 3 (September 2017) - Fumimoto, Tomoko; Ueyama, Takeshi; Shimizu, Akihiko; Yoshiga, Yasuhiro; Ono, Makoto; Kato, Takayoshi; Ishiguchi, Hironori; Okamura, Takayuki; Yamada, Jutaro; Yano, Masafumi
Abstract: Background: There is little information about the relationship between J waves and the occurrence of ventricular fibrillation (VF) in patients with vasospastic angina (VSA). The present study aimed to assess the incidence of J waves and the occurrence of VF in patients with VSA. Methods: The subjects consisted of 62 patients with VSA diagnosed by acetylcholine provocation tests in our institution from 2002 to 2014. We investigated the VF events, prevalence of J waves, and relationship between the VF events and J waves. Results: J waves were observed in 16 patients (26%) and VF events were documented in 11 (18%). The incidence of VF in the patients with J waves was significantly higher than that in those without J waves (38% vs 11%, p  = 0.026). J waves were observed in the inferior leads in 14 patients, lateral leads in 5, and anterior leads in 3. A univariate analysis indicated that the incidence of VF in the inferior leads of J wave positive patients (46% = 6/14) was significantly ( p  = 0.01) higher than that in the inferior leads of J wave negative patients (10% = 5/48). The J waves in the anterior and/or lateral leads were not related to the incidence of VF. Notched type and slurred type J waves were not associated with VF. A multivariate analysis revealed that J waves in VSA patients were associated with VF [odds ratio (OR) 6.41, 95% confidence interval (CI) 1.37–29.93, p  = 0.02] and organic stenosis (OR 6.98, 95% CI 1.39–35.08, p  = 0.02). Further, J waves in the inferior leads were strongly correlated with VF (OR 11.85, 95% CI 2.05–68.42, p  = 0.006). Conclusions: The results suggest that the existence of J waves, especially in the inferior leads, might be a risk factor for VF in VSA patients.